PENGARUH LINGKUNGAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CV. WIJAYA STEEL MANDIRI DI GIANYAR - Ni Komang Trinanda Saradewi; Ni Wayan Eka Mitariani; I Gusti Ayu Imbayani (EMAS, 2022)
Wijaya Steel Mandiri in Gianyar is a company that is developing in the field of lightweight steel roof construction and developing its production in the form of trimdeck, battens and hollow. Where there is a problem that occurs, namely a decrease in target achievement, which is caused by several problems, namely the phenomena contained in the work environment, the lack of lighting in the production room and poor air circulation, making employees less work optimally and the phenomenon of job satisfaction seen from where their salary is. acceptance is still below standard, especially in the marketing department and employees also complain because they feel they have worked for a long time and have made a good contribution but did not get a proper promotion. This study aims to obtain empirical evidence between the effect of work environment and job satisfaction on employee performance at CV. Wijaya Steel Mandiri in Gianyar. The total of samples taken is 40 employees from CV. Wijaya Steel Mandiri in Gianyar City, with taking all employees as respondent. Data collection is done through interviews, observations, document studies, and distributing questionnaire. Multiple linear regression, multiple correlation analysis, analysis of determination, T Test and F Test are used as analysis techniques in this research. Research results shows that working environment and job satisfaction gives positive and significant impact towards employees working performance at CV. Wijaya Steel Mandiri in Gianyar City. Multiple correlation analysis result shows that there is a strong relationship between work environment and job satisfaction towards employee working performance. T Test result concludes that working environment significantly impacts (real) employee working performance, and it is said that job satisfaction significantly impacts employee working performance. Furthermore, F Test results shows that work environment and job satisfaction have simultaneous and significant impact towards employee working performance.